Case reportAnaesthesia of a patient after organ transplantation for total hip arthroplasty. Case report - Ćwiek, Renata; Lisowska, Barbara; Małdyk, Paweł (Reumatologia/Rheumatology, 2006)
The article reviews the anaesthesia and perioperative management of a liver and kidney transplanted patient who underwent total hip arthroplasty. The 48-year-old liver and kidney recipient with insulin-dependent diabetes and mild hypertension was scheduled for total hip arthroplasty under spinal anaesthesia. Recommended immunosuppressive and antibiotic treatment was continued. Operative and post-operative details were recorded, including basic life parameters, hourly diuresis as well as biochemical parameters. Surgery and the post-operative period were not complicated. On the 24th day of hospitalization the patient was discharged from hospital in a good condition.